2020
DOI: 10.1038/s41420-020-00302-1
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of ANT1 confers oncogenic properties to rhabdomyosarcoma tumor cells by modulating metabolism and death pathways

Abstract: Rhabdomyosarcoma (RMS) is the most frequent form of pediatric soft-tissue sarcoma. It is divided into two main subtypes: ERMS (embryonal) and ARMS (alveolar). Current treatments are based on chemotherapy, surgery, and radiotherapy. The 5-year survival rate has plateaued at 70% since 2000, despite several clinical trials. RMS cells are thought to derive from the muscle lineage. During development, myogenesis includes the expansion of muscle precursors, the elimination of those in excess by cell death and the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Previous studies have suggested deregulation of oxidative stress in ERMS [ 10 , 29 , 30 ]. We therefore examined mitochondrial Ca 2+ uptake, oxygen consumption rate (OCR) and adenosine triphosphate (ATP)-linked respiration in three patient-derived ERMS cell lines (RD, RD18 and JR1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested deregulation of oxidative stress in ERMS [ 10 , 29 , 30 ]. We therefore examined mitochondrial Ca 2+ uptake, oxygen consumption rate (OCR) and adenosine triphosphate (ATP)-linked respiration in three patient-derived ERMS cell lines (RD, RD18 and JR1).…”
Section: Resultsmentioning
confidence: 99%
“…We found that SLC25A4 and SLC25A23 were respectively decreased in gastric cancer and colon cancer, while SLC25A7 was increased in gastric cancer, which was consistent with our bioinformatic prediction. It has been shown that the ANT1 protein encoded by SLC25A4 was low expressed in rhabdomyosarcoma [7]. Combining with this, SLC25A4 is located in mitochondria and involved in metabolic process by regulating ATP/ADP.…”
Section: Discussionmentioning
confidence: 97%
“…This may be related to the few samples or the existence of posttranscriptional regulation. It has been shown that the ANT1 protein encoded by SLC25A4 was also lowly expressed in rhabdomyosarcoma [ 13 ]. Combining with this, ANT1 transports ADP to mitochondrial matrix and synthesizes ATP there, then exports it to the cytoplasm to provide fuel for the metabolic energy process [ 14 ].…”
Section: Discussionmentioning
confidence: 99%